Monomer-trimer equilibrium of the ectodomain of SIV gp41: insight into the mechanism of peptide inhibition of HIV infection. - Caffrey, M. (Cold Spring Harbor Laboratory Press, 1999)
The monomer-trimer equilibrium of the ectodomain of SIV gp41 (residues 27-149, e-gp41) has been characterized by analytical ultracentrifugation, circular dichroism (CD), and NMR spectroscopy. Based on analytical ultracentrifugation experiments performed at different rotor speeds and protein concentrations, the equilibrium association constant for the SIV e-gp41 trimer is 3.1 x 10(11) M(-2). The presence of intermolecular nuclear Overhauser effects in a mixture of 12C and 13C-labeled e-gp41 prepared under nondenaturing conditions unambiguously demonstrates that there is a dynamic equilibrium between the monomer and trimer. The CD spectra taken as a function of SIV e-gp41 concentration suggest that the helical content of the monomeric state does not change significantly relative to that of the trimeric state. The relevance of the monomer-trimer equilibrium is discussed with respect to gp41 function and the inhibitory properties of gp41 peptides.